Avaliação da integridade de tesouras de caibro armado de madeira do século XIX através de ensaios não-destrutivos - Larissa Camilo de Souza Lima e Silva (2019)
The technologies used in the coverage systems of the Brazilian colonial period are inheritances of the engineering developed in the colonizing countries. Portugal as the main colonizing country of Brazil, contributed in the then colony constructive technologies that brought the two cultures closer together. The composition of the symmetry and volumetry of the buildings of the cities of Braga, Porto and Guimarães are similar to the cities of Ouro Preto, Mariana and São João Del Rey. The immigration of engineers, architects and military personnel from the north of Portugal mining region. Among the constructive knowledge inherited by the work masters, the types of coverage were highlighted. The level donkeys were adapted to the regionalism of Minas Gerais as armor-sheared scissors, which in fact determined the exuberant execution of the linings and adornments inside the religious buildings. However, wood, as organic and heterogeneous material, requires careful inspections to determine the most appropriate methods for the maintenance of its elements. Non-destructive methodologies are essential for the preservation actions of the built cultural patrimony, since they allow the application of methods of inspection without the degradation of the material. In this context, the elaboration of an inspection methodology that includes physical and mechanical variables of the old roofs considering the difficult access to the wood elements, the instability of the typology, the historicity of the constructive system and the fragile state of the art of constructions are of great importance for the preservation of historic buildings. This thesis presents a non-destructive methodology using the methods of active thermography, acoustic tomography and x-ray in the inspection of the integrity of a scissors of the Church of the Blessed Sacrament of the city of Jequitibá, Minas Gerais, investigating the historicity of the constructive system of armed bandit and its Portuguese roots.